When survival matters: is decreasing survival underlying the decline of common pochard in western Europe?. Issue 3 (16th September 2020) - Folliot, Benjamin; Souchay, Guillaume; Champagnon, Jocelyn; Guillemain, Matthieu; Durham, Maurice; Hearn, Richard; Hofer, Josef; Laesser, Jacques; Sorin, Christophe; Caizergues, Alain
Abstract : In western Europe, common pochard populations have experienced a sharp decline over the last two decades, together with an increasing proportion of males. Both of these changes were suggested to result from decreasing survival of nesting females (i.e. survival of adult females) owing to increasing predation pressure. To test this hypothesis, we used capture–mark–recapture/recovery data of common pochard ringed during autumn–winter (October–February) in three countries of western Europe (Switzerland, United Kingdom and France). We found no evidence for decreasing survival of individuals ringed in the United Kingdom or in Switzerland over the long term (1977–2011). In France, adult males and juvenile females experienced significant decreasing survival over a shorter interval (2004–2017). Overall, females displayed lower survival than males, although this was only weakly supported by the French dataset. In contrast, only sex differences and no age differences in survival rates were recorded in the UK and Switzerland (females 0.67 ± 0.03 and 0.69 ± 0.03; males: 0.81 ± 0.01 and 0.75 ± 0.01, respectively), while both age and sex differences were recorded for France (adult females 0.62 ± 0.07, adult males 0.66 ± 0.07, juvenile females 0.49 ± 0.08, juvenile males 0.54 ± 0.08). Therefore, decreasing survival of adult females was unlikely the underlying cause of the decline of common pochard populations in western Europe. Using an age‐structured two‐sex matrix population model, we show that when adult males experience higher survival than adult females (as it is the case for common pochards), decreasing survival of nests and/or juveniles can trigger decreasing population size and increasing proportions of males at the same time.